"Memorization and Memorialization: 'The Burial of Sir John Moore after Corunna' " - Robson, Catherine (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThis article addresses the rubric of "memory and materiality" by considering how works of literature held within individual minds might have contributed to material changes in the world at large. For a good proportion of both the nineteenth and twentieth centuries, the most important relationship between literature and millions of English-speaking people was created by one particular pedagogical regimen: the memorization and recitation of short poetic pieces. I take as my test case a single work from the schoolroom canon—Charles Wolfe's 1817 poem, "The Burial of Sir John Moore after Corunna"—and examine the various ways in which lines and phrases from these verses were explicitly or implicitly cited by people caught up in the bloody turmoil of the American Civil War, the conflict which first witnessed the widespread development of state-sponsored practices to commemorate the corpses of common soldiers. I argue here that the presence of Wolfe's poem in the minds of ordinary individuals played its part in creating the social expectations that led to the establishment of the National Cemeteries in the United States, and thus, in due course, the mass memorialization of World War I.